2007
DOI: 10.1002/mnfr.200700024
|View full text |Cite
|
Sign up to set email alerts
|

The bioavailability of raspberry anthocyanins and ellagitannins in rats

Abstract: The fate of anthocyanins and ellagitannins in rats was monitored following ingestion of raspberry juice. After 1 h low nM concentrations of unmetabolised anthocyanins were present in plasma but these declined by 2 h and after 4 h they were no longer detectable. For the first 2 h there was an almost full recovery of anthocyanins as they passed from the stomach through the duodenum/jejunum and into the ileum. After 3 h less than 50% were recovered, and the levels declined rapidly thereafter. Excretion of raspber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
79
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 39 publications
6
79
0
Order By: Relevance
“…27) Ellagitannins were not detectable in the plasma, in contrast to the metabolites, ellagic acid (m=z 301/ 284), urolithin A-glucuronide (m=z 403/227), and urolithin C-glucuronide (m=z 419/243), these results being consistent with reports from other authors. 17,18) We have previously reported a similar antihypertensive effect of proanthocyanidins from persimmon leaf tea without any identification of the absorbed components, 28) but in this study, we could prove that absorbed proanthocyanidin short-chain oligomers with vasorelaxant activity were the active antihyperetensive components.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…27) Ellagitannins were not detectable in the plasma, in contrast to the metabolites, ellagic acid (m=z 301/ 284), urolithin A-glucuronide (m=z 403/227), and urolithin C-glucuronide (m=z 419/243), these results being consistent with reports from other authors. 17,18) We have previously reported a similar antihypertensive effect of proanthocyanidins from persimmon leaf tea without any identification of the absorbed components, 28) but in this study, we could prove that absorbed proanthocyanidin short-chain oligomers with vasorelaxant activity were the active antihyperetensive components.…”
Section: Discussionmentioning
confidence: 57%
“…These compounds have also been reported to have vasorelaxant activity during in vitro rat aorta experiments, 15,16) although their oral absorbability was reported to be very poor. 17,18) PAs and ETs occur together in such edible fruits and nuts as boysenberry, 14) raspberry, 5) strawberry, 19) and walnut. 6) There has been only one recent report on the in vivo antihypertensive y To whom correspondence should be addressed.…”
mentioning
confidence: 99%
“…Along with being rich in polyphenols and other antioxidants, including anthocyanins and Vitamin C, they are distinguished by containing large amounts of ellagitannins which account for over half of their antioxidant capacity [17]. Current measures of the pharmacokinetics and bioavailability of ellagitannins indicate that they are poorly absorbed in humans and rats, suggesting that they may possibly exert the majority of their effects within the gastrointestinal tract [17,23,36]. Diverse arrays of dietary components have been tested as agents for moderating inflammation and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Red raspberries are rich in macro and micro nutrients and have a unique profile of polyphenols, rating high in ellagitannins and anthocyanins [23,24]. Whole fruit preparations as well as isolated components have demonstrated beneficial effects, in vitro and in vivo, including antimutagenicity, antiangiogenesis, and antioxidant capacity [10,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Except for the studies of Cerdá et al (2003aCerdá et al ( & 2003b reporting trace amounts of punicalagin in rat plasma after a high daily consumption of 0.9 g punicalagin for 37 days, many in vivo animal studies indicate that ETs are not found as such in the blood circulation (Borges et al, 2007;Cerdá et al, 2004aCerdá et al, & 2004bEspín et al, 2007;González-Barrio et al, 2010;Mertens-Talcott et al, 2006;Seeram et al, 2006). In their pig study, Espín et al (2007) reported that animals fed with acorns rich in ETs and EA (single feeding) showed the occurrence of urolithin A and B as aglycone and conjugates in their plasma 24h, but not 3h, after ingestion.…”
Section: Blood Circulation Distribution and Excretionmentioning
confidence: 99%